Dynamic localization of DNA topoisomerase I and its functional relevance during Drosophila development. - Huang, W.; Liu, Z.; Rong, Y.S. (G3 : genes - genomes - genetics, 2021)
DNA topoisomerase I (Top1) maintains chromatin conformation during transcription. While Top1 is not essential in simple eukaryotic organisms such as yeast, it is required for the development of multicellular organisms. In fact, tissue and cell-type-specific functions of Top1 have been suggested in the fruit fly Drosophila. A better understanding of Top1's function in the context of development is important as Top1 inhibitors are among the most widely used anticancer drugs. As a step toward such a better understanding, we studied its localization in live cells of Drosophila. Consistent with prior results, Top1 is highly enriched at the nucleolus in transcriptionally active polyploid cells, and this enrichment responds to perturbation of transcription. In diploid cells, we uncovered evidence for Top1 foci formation at genomic regions not limited to the active rDNA locus, suggestive of novel regulation of Top1 recruitment. In the male germline, Top1 is highly enriched at the paired rDNA loci on sex chromosomes suggesting that it might participate in regulating their segregation during meiosis. Results from RNAi-mediated Top1 knockdown lend support to this hypothesis. Our study has provided one of the most comprehensive descriptions of Top1 localization during animal development.